Uvedba programa "Skrb za bolnikovo kri" v vsakodnevno klinično prakso - Bitenc, Marko (Zdravniški vestnik, 2020)
Transfusion after a surgical procedure elevates risk for perioperative complications, prolongs hospital stay and worsens the outcome of surgical treatment. Undefined and untreated preope - rative anaemia presents an independent factor for perioperative complications and transfusion in the perioperative period. Before surgery, we must identify patients at higher risk for anaemia and adjust preoperative preparation, surgical technique and postoperative treatment accordin- gly. The "Patient Blood Management" (PBM) programme is established in many European countries and supported by a directorate of the European Commission. It is concerned with the treatment of anemia, optimization of haemostasis and measures to reduce the need for blood transfusion. The three pillars of PBM are: (1) optimal haematopoiesis, (2) reduced iatrogenic blood loss and (3) improved patients' tolerance for anaemia. In this article we analyse the proportion of patients that came for surgery to the observed surgical institution in an anaemic state in a two-year period and how many of them needed blood transfusion. We also describe the foundations of the PBM program and a plan to implement it in everyday clinical practice.
Keywords: anemija pred operacijo; blood loss; izguba krvi; preoperative anaemia; transfusion; transfuzija